Analisis Nilai Budaya dan Nilai Sosial pada Tradisi Arak-arakan Rujukan di Kampung Cipeucang sebagai Bahan Pembelajaran Projek Penguatan Profil Pelajar Pancasila (Kearifan Lokal) di SMA - Aulia, Novi (Universitas Mathla'ul Anwar Banten, 2023)
This research aims to describe the cultural values and social values in the reference procession tradition in Cipeucang village as learning material for Pancasila student projects, especially in high school. This research was carried out based on a qualitative approach with descriptive methods that focused on content analysis. The data and data sources in this research are in the form of text, such as: words, phrases, sentences and conversations related to cultural values and social values. The instrument used in this research was the researcher himself with a theory validation test. Based on the description of the results of the analysis of the